REPRESENTASI MEME JOMBLO DALAM SITUS JEJARING SOSIAL TWITTER (ANALISIS SEMIOTIKA ROLAND BARTHES) - Cindy, Natasha; ", Yasir (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Internet usage in Indonesia for accessing social networks is quite high, one of them is the usage of Twitter social networking. There are a new things that become a trend in recent years, it‟s a meme which is become a new culture on the internet .Single meme is one that caught the atttention of netizens, jomblo are often we hear in everyday life. This study aims to determine how the meaning of denotation, conotation and myth are represented in single meme on Twitter social networking.Method of this resesearch is qualitative research method with Roland Barthes‟ semiotic approach. Data was collected through documentation,and library research. Data analysis unit in this research consist of 2 comparasion of meme jomblo and 2 non comparasion of single meme which is often share in Twitter.Based on this research represented tha the main character of single meme is always a man. Single status is also often compared to dating people and long distance relationship. Single status is closely associated with the internet, the internet became the savior of the life of a single. Women in single meme represented as a women who is materialistic.Keywords : Representation, Jomblo Meme, Twitter, Semiotic.